Loss of a newly discovered microRNA in Chinese hamster ovary cells leads to upregulation of N‐glycolylneuraminic acid sialylation on monoclonal antibodies. Issue 3 (14th January 2022) - Fischer, Simon; Mathias, Sven; Stadermann, Anna; Yang, Shumin; Schmieder, Valerie; Zeh, Nikolas; Schmidt, Nicoletta; Richter, Patrick; Wright, Sara; Zimmermann, Eike; Ley, Yan; van der Meer, Julia; et al.
Abstract: Chinese hamster ovary (CHO) cells are known not to express appreciable levels of the sialic acid residue N‐glycolylneuraminic acid (NGNA) on monoclonal antibodies. However, we actually have identified a recombinant CHO cell line expressing an IgG with unusually high levels of NGNA sialylation (>30%). Comprehensive multi‐OMICs based experimental analyses unraveled the root cause of this atypical sialylation: (1) expression of the cytidine monophosphate‐N‐acetylneuraminic acid hydroxylase ( CMAH ) gene was spontaneously switched on, (2) CMAH mRNA showed an anti‐correlated expression to the newly discovered Cricetulus griseus (cgr) specific microRNA cgr ‐miR‐111 and exhibits two putative miR‐111 binding sites, (3) miR‐111 expression depends on the transcription of its host gene SDK1, and (4) a single point mutation within the promoter region of the sidekick cell adhesion molecule 1 ( SDK1 ) gene generated a binding site for the transcriptional repressor histone H4 transcription factor HINF‐P . The resulting transcriptional repression of SDK1 led to a downregulation of its co‐expressed miR‐111 and hence to a spontaneous upregulation of CMAH expression finally increasing NGNA protein sialylation. Abstract : Fischer and co‐workers identified a mAb producing CHO cell line exhibiting unusually high levels of potentially immunogenic NGNA sialylation. A comprehensive multi‐OMICS based root cause analysis revealed that the CMAH gene was upregulated as a result of a point mutation identified in the promoter region of the SDK1 gene which led to the silencing of its intronic miR‐111. MiR‐111 has been discovered as a new regulatory RNA in CHO cells responsible for CMAH gene and thus sialylation regulation.